Comparison of soybean hull pre-treatments to obtain cellulose and chemical derivatives: Physical chemistry characterization - Camiscia, Paola (2018)
The cellulose from soybean hull, a waste without value from the argentine agriculture, was successfully obtained by using two different treatments: the traditional alkaline-bleaching pathway and from a simple pre-alkaline treatment at low temperatures. The comparison of both methods yielded similar results regarding its ability to open the lignin cellulosic structure of the hull and the total elimination of the lignin content. Fourier Transform Infrared spectroscopy (FT-IR), Thermogravimetric analysis (TGA), Scanning electron microscopy (SEM), 13C nuclear magnetic resonance (13C-RMN) and Raman spectroscopy were used to characterize the structures and the properties of cellulose. The results showed that cellulose can be easily obtained with just an alkaline pre-treatment of 5% (w/v) NaOH during 40 h at 50 °C and free of any lignin content. The attachment of different functional groups, such as -COOH and (CH3)3N+, changed the physicochemical properties of the obtained cellulose, showing mayor crystalline structure, and consequently modifying the swelling capacity and its ability to adsorb model proteins.